The Influence Of Price Location And Service Quality On Purchasing Decisions (Case Study At The Naja Putra Demak Clothing Store) - Nurkholifah, Umi; Nurhayati , Nurhayati; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
This research aims to examine the influence of location, price and service quality on purchasing decisions (Study at the Naja Putra Demak Clothing Store). The population in this study includes all consumers who shop at the Naja Putra Demak Clothing Store. The data source used is primary data, this sampling technique uses a purposive sampling method or sample determination with certain considerations, namely respondents who have shopped at the Naja Putra Demak Clothing Store. Using a sample size of 102 respondents. The analytical method for this research uses multiple linear regression analysis using the data processing tool SPSS (Statistical Product and Service Solution) Version 26. The results of this research show that the location variable (X1) has a positive and significant effect on purchasing decisions (Y), price (X2) has a positive and significant effect on purchasing decisions (Y), service quality (X3) does not have a positive and significant effect on purchasing decisions ( Y). then simultaneously and together it can be concluded that Location (X1), Price (X2) and Service Quality (X3) have a positive and significant effect on Purchasing Decisions (Y).